2022
DOI: 10.1007/s10919-022-00399-1
|View full text |Cite
|
Sign up to set email alerts
|

Imagining is Not Observing: The Role of Simulation Processes Within the Mimicry-Liking Expressway

Abstract: Individuals automatically mimic a wide range of different behaviors, and such mimicking behavior has several social benefits. One of the landmark findings in the literature is that being mimicked increases liking for the mimicker. Research in cognitive neuroscience demonstrated that mentally simulating motor actions is neurophysiologically similar to engaging in these actions. Such research would predict that merely imagining being mimicked produces the same results as actually experiencing mimicry. To test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This implies that the positive effects of BeMim arise because of a basic contingency between self-movement and the other's movement, regardless of whether that movement is actually mimicry. Other studies also showed similar effects indicating that merely responding to another person's movement might be enough to induce the liking effect, without the need to mimic the same movements (Sparenberg et al, 2012;Kulesza et al, 2022).…”
Section: Studying Motor Bemim With Controlled Movement Paradigmsmentioning
confidence: 76%
See 2 more Smart Citations
“…This implies that the positive effects of BeMim arise because of a basic contingency between self-movement and the other's movement, regardless of whether that movement is actually mimicry. Other studies also showed similar effects indicating that merely responding to another person's movement might be enough to induce the liking effect, without the need to mimic the same movements (Sparenberg et al, 2012;Kulesza et al, 2022).…”
Section: Studying Motor Bemim With Controlled Movement Paradigmsmentioning
confidence: 76%
“…Similarly, another issue is whether BeMim effects arise only when there is precise mimicry between participant and confederate (the same limb performing the same action) or if more general contingent responses with any limb are enough to lead to BeMim effects. Some previous studies suggest that merely responding to another person's movement might be enough to induce the BeMim liking effect, without the need to mimic the same movements (Sparenberg et al, 2012;Kulesza et al, 2022). The implications of these results for our theories will be considered in the section about BeMim neurocognitive mechanisms.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The literature demonstrates that mimicry positively influences the perception of the mimicker (e.g., Chartrand and Bargh, 1999 ; Kulesza et al, 2022a ), and this effect can spillover to the products ( Tanner et al, 2008 ; Kulesza et al, 2017 ), and to the entire company/organization that the mimicker represents ( Jacob et al, 2011 ). The presented studies correspond to the research gap related to mimicry and its spillover potential by systematically verifying, in different contexts, the issue of spillover effects of mimicry and conceptually replicating the result previously reported by Jacob et al (2011) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, humans perform mimicry from the very first hours after being born [ 19 ]. Later in life we mimic each other to be accepted [ 20 ], liked [ 4 , 21 , 22 ], helped [ 23 25 ], and trusted [ 26 , 27 ]. Since mimicry is such a common behavior, it is postulated that mimicry is responsible for creating and maintaining social relations; it acts as a “social glue” [ 5 , 28 ] among us making this process one of the most fundamental, among many others.…”
Section: Introductionmentioning
confidence: 99%